Perceptions of Leading as Learners. Phase One: Discovery - Wood, Kevin (International Journal of Education Policy and Leadership, 2025)
Ten school-based leaders engaged in an experimental professional learning community to understand when, during their daily practice, they placed learning (as an action) at the forefront of their leadership. This article presents the findings from the first phase (discovery) of a four-phase, two-year appreciative inquiry study. At their schools, the participants attempted to act as learners and nurture the learning process as a method of leadership. These findings suggest that when leaders are open, they are constructing leadership, they are supportive of others, and their efforts build community. One major insight encountered during the study was discovering how the technocratic organization of schooling can inhibit a leader being a learner. The aim of the study was to deepen the understanding of how school leaders approach dispositions of learning.